Florida Crop/Pest Management Profile: Specialty Brassicas (Arrugula, Bok Choy, Chinese Broccoli, Chinese Mustard, Napa) - Mark A. Mossler (EDIS, 2005)
Since leafy brassicas are vegetative crops, the most important pest groups in Florida production include the early season diseases, weeds, and leaf-feeding insects. Mites, viruses, and nematodes are generally not problematic in Florida leafy brassica production. This document is PI-70, one of a series of publications of the Pesticide Information Office, Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published November 2005.